Job Autonomy and Teacher Career Commitment in Educational - Olievia Prabandini Mulyana; Umi Anugerah Izzati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Study aims to determine the relationship between job autonomy and teacher career commitment in educational. This study used quantitative method and the study design is correlation study. The sampling technique used is accidental sampling to the population of teachers in an educational foundation with minimum a year work period. The participants of this study are 191 teachers from educational background. The data collection used job autonomy scale and teacher career commitment scale in a likert scale model and data analyzed using a statistical test of product moment correlation with SPSS program. The results of the study shown that there is a significant positive relationship between job autonomy and teacher career commitment. In other words, the higher the autonomy of the job for teacher, the higher their career commitment. Otherwise, the lower the teacher job autonomy, the lower the teacher’s career commitment too. This study shows that job autonomy and career commitment have a significant relationship that can interconnect by each other in term of professional career as teacher.